2000
DOI: 10.1046/j.1432-1327.2000.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression in yeast and tobacco of plant cDNAs encoding acyl CoA:diacylglycerol acyltransferase

Abstract: During the course of a search for cDNAs encoding plant sterol acyltransferases, an expressed sequence tag clone presenting substantial identity with yeast and animal acyl CoA:cholesterol acyltransferases was used to screen cDNA libraries from Arabidopsis and tobacco. This resulted in the isolation of two full-length cDNAs encoding proteins of 520 and 532 amino acids, respectively. Attempts to complement the yeast double-mutant are1 are2 defective in acyl CoA:cholesterol acyltransferase were unsuccessful, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(183 citation statements)
references
References 53 publications
10
173
0
Order By: Relevance
“…It is somewhat surprising, however, that the two identified DGATs are members of gene families that do not share obvious homology. Interestingly, both the DGAT1 and the DGAT2 gene families have phylogenetic relatives dating back to yeast, and both enzymes have homologues that function as DGATs in plants (9,10). 2 It seems likely that a DGAT2 homologue in yeast (GenBank TM accession number CAA99466) contributes to the triglyceride synthesis activity not accounted for by lecithin:diacylglycerol acyltransferase activity, which appears to be the major triglyceride synthesis activity in this organism (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is somewhat surprising, however, that the two identified DGATs are members of gene families that do not share obvious homology. Interestingly, both the DGAT1 and the DGAT2 gene families have phylogenetic relatives dating back to yeast, and both enzymes have homologues that function as DGATs in plants (9,10). 2 It seems likely that a DGAT2 homologue in yeast (GenBank TM accession number CAA99466) contributes to the triglyceride synthesis activity not accounted for by lecithin:diacylglycerol acyltransferase activity, which appears to be the major triglyceride synthesis activity in this organism (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a DGAT was isolated by protein purification in the fungus M. rammaniana (26). The gene encoding this DGAT (MrDGAT2A) has no sequence homology with members of the DGAT1 family, including genes related to plant DGAT1 (9,10). Using sequences of the newly identified fungal DGAT to perform homology searches of EST data bases, we identified a family of related genes in mammalian species (Fig.…”
Section: Identification Of a Second Dgat Activity In Dgatmentioning
confidence: 99%
“…Two classes of genes encode DGATs in plants, DGAT1 and DGAT2, and these are homologous to those found in fungi and mammals (42). Genetic studies with mutants have confirmed that DGAT1 is required for normal TAG accumulation in oilstoring tissues of Arabidopsis (43), and its overexpression in vegetative tissues or seeds can lead to enhanced TAG accumulation (44,45). However, disruption of DGAT1 gene function results in only a 20 -40% reduction in Arabidopsis seed oil, so other mechanisms must cooperate in the accumulation of TAG in plants.…”
Section: Conventional Kennedy Pathwaymentioning
confidence: 94%
“…Animals with reduced DGAT activity are resistant to diet-induced obesity Smith et al, 2000) and lack milk production (Smith et al, 2000). Over-expression of DGAT enzymes increases TAG content in plants (Andrianov et al, 2010;Bouvier-Nave et al, 2000;Burgal et al, 2008;Durrett et al, 2010;Jako et al, 2001;Lardizabal et al, 2008;Xu et al, 2008), animals (Kamisaka et al, 2010;Liu et al, 2009;Liu et al, 2007;Roorda et al, 2005), and yeast (Kamisaka et al, 2007). DGATs have nonredundant functions in TAG biosynthesis in species such as mice (Stone et al, 2004) and tung tree (Vernicia fordii) (Shockey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%